2016
DOI: 10.2224/sbp.2016.44.4.631
|View full text |Cite
|
Sign up to set email alerts
|

Family Life Satisfaction Scale—turkish Version: Psychometric Evaluation

Abstract: My aim was to adapt the Family Life Satisfaction Scale, which was developed by Barraca, Yarto and Olea (2000), for use with a Turkish sample and to examine the adapted scale's reliability and validity. In Study 1, I administered the translated scale to 441 participants from a range of age groups, and in Study 2 the finalized scale's reliability and validity were assessed with a separate sample (N = 506). Further, in Study 3, I examined the convergent validity of the FLSS by comparing it with the Satisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Indeed, one study showed that positive affect predicted high school students’ satisfaction with family life [ 151 ]. On the other hand, other studies identified family satisfaction as a significant predictor of life satisfaction [ 170 , 171 , 172 , 173 ]. For instance, some authors [ 36 , 149 ] found that high satisfaction with family life was related to a greater frequency and intensity of affective experiences of love, affection, joy, and happiness [ 174 ].…”
Section: Resultsmentioning
confidence: 97%
“…Indeed, one study showed that positive affect predicted high school students’ satisfaction with family life [ 151 ]. On the other hand, other studies identified family satisfaction as a significant predictor of life satisfaction [ 170 , 171 , 172 , 173 ]. For instance, some authors [ 36 , 149 ] found that high satisfaction with family life was related to a greater frequency and intensity of affective experiences of love, affection, joy, and happiness [ 174 ].…”
Section: Resultsmentioning
confidence: 97%
“…The reliability of the scale for our sample (Cronbach’s α) was 0.93. This scale has already been adapted and administered in a Portuguese population of families with children in the fourth grade ( 30 ), a Mexican population of children and adolescents ( 31 ), and a Turkish sample of youth and adults ( 32 ) proving strong validity and reliability.…”
Section: Methodsmentioning
confidence: 99%
“…Demographic questionnaire: This 13-item questionnaire was developed by the researchers based on previous literature [1][2][3][4][5][6][7][21][22][23] to determine the demographic characteristics of the participants, including school year, gender, age, number of siblings, perceived family income, perceived parental attitudes, parents' educational background, parents' working status, parental living together and perceived academic achievement.…”
Section: Inclusion Criteriamentioning
confidence: 99%